Analisis Karakteristik, Partisipasi, dan Sikap Komunitas terhadap Program CSR PT Pelindo III - Tuhfatul Mubarokah Assalamah; Nur Hidayatus Syarifah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This study evaluates the impact of PT Pelindo III's Corporate Social Responsibility (CSR) program in Kampung Lawas Maspati, particularly the Taman Baca facility, on community characteristi, participation, and attitudes. Using a quantitative approach with a survey design, data was collected from 70 respondents, including demographic characteristics, participation levels, and attitudes towards the CSR program. Results show that the CSR program significantly increased community participation, with a cumulative participation rate of 78.75%. The community displayed a positive attitude towards the program, with the conative dimension reaching 36.47%, indicating a desire to engage actively. The study concludes that PT Pelindo III’s CSR program effectively enhances literacy and community empowerment and suggests further research to explore factors influencing attitudes and the long-term impacts of the program.